Growth performance of Large White Yorkshire pigs on supplementation of Jaggery filter cake in finisher stage - PATEL, B H M; KUMAR, SANJAY; PRASANNA, S B (The Indian Journal of Animal Sciences, 2019)
The present study was conducted on 24 growers which were divided into 4 dietary treatment groups, viz. Group 1: concentrate only, Group 2: concentrate +700 g JFC, Group 3: concentrate + 1,400 g JFC, Group 4 and concentrate + 2,100 g JFC. Jaggery filter cake supplementation was increased every week in the ratio of 0:50:100:150 g in group 1, 2, 3, 4 respectively. Lowest and highest dry matter intake was observed in group 1 and group 4 respectively and values differed significantly (P<0.01). At the end of finisher stage, group 4 showed highest body weight followed by group 2, 3 and 1. The overall FCR during growing stage was 2.96 ± 0.04, 2.93± 0.02, 2.95 ± 0.04 and 3.05± 0.05 in group 1, 2, 3 and 4 respectively. It can be concluded that Jaggery Filter cake can be fed to finisher pigs starting with 2,100 g and increment of 150 g in the subsequent weekly interval for optimal growth rates.